The mysterious island - Abbott, Tony.; Merrell, David Webber, 1973- (New York : Scholastic, 1999)
Eric, Julie, Neal and Princess Keeah are shipwrecked on an island belonging to one of Lord Sparr's witches after being caught in a magical ocean storm.
"A Little Apple paperback."
"RL: 3"--P. [4] of cover.
"007-010"--P. [4] of cover.
460
Accelerated Reader AR
Keywords: Droon (Imaginary place) -- Juvenile fiction; Fantasy fiction